In vitro evaluation of kinnow waste as substitute of cereal grains in the concentrate mixture and empty pea pods as that of berseem hay in total mixed ration for livestock - BAKSHI, M P S; HUNDAL, J S; WADHWA, M (The Indian Journal of Animal Sciences, 2020)
This study was taken up to assess the extent to which kinnow mandarin (Citrus reticulata) waste (KW) could substitute cereal grains in the concentrate mixture and empty pea (Pisum sativum) pods (EPPs) as that of berseem (Trifolium alexandrium) hay in total mixed ration (TMR) for livestock. In the first experiment, sundried finely ground kinnow waste replaced barley grains on N basis at 0, 25, 50, 75 and 100% levels in concentrate mixtures. The comparable N-content indicated that the concentrate mixtures were iso-nitrogenous. The EE and cell wall constituents (CWC) increased linearly with the increase in level of KW. The replacement of barley with KW did not affect net gas production (NGP), true OM digestibility and ME availability up to 50% level of replacement. Total and individual volatile fatty acids (VFAs) and microbial biomass production improved up to 50% level of replacement but declined thereafter. In the second experiment, sundried finely ground EPPs replaced berseem hay on N basis at 0, 25, 50, 75 and 100% levels in TMR. The EE and CWCs content was not affected up to 50% level but thereafter EE content decreased, whereas CWCs content increased. The NGP, digestibility of true DM and OM, VFAs production, ME availability and microbial biomass synthesis improved up to 50% level of replacement of berseem hay with EPPs, thereafter it declined. The hydrogen recovery, hydrogen consumption and fermentation efficiency were not affected upto 50% level of EPPs but at higher levels these parameters were depressed. Therefore, KW could replace barley grains in concentrate mixture while EPPs could replace berseem hay in TMR up to 50% level without affecting nutrient utilization, VFA production, ME availability and microbial biomass production under in vitro conditions.